PERANCANGAN SISTEM OTOMATIS PENGATUR SUHU DAN KELEMBABAN PADA KANDANG JANGKRIK DI DAERAH MASARAN SRAGEN BERBASIS MIKROKONTROLLER ARDUINO - Firdausi, Muhammad Tsatsa; Rohmah, Ratnasari Nur (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The control system is a technology that can be used to facilitate human activities in daily life. One of the problems that exist is that there are still many cricket farms using control of temperature and humidity of the cage which is still being carried out with estimates and usage manual control of temperature and humidity. Manual control of cricket cages and with only estimates having the weakness that the temperature and humidity of the cage cannot be regulated with certainty. With based on these problems, came the idea to conduct research on system design automatic control of temperature and humidity in cricket cages. The design of this automated system uses The main components include Arduino UNO as a microcontroller, DHT22 sensor as a temperature reader and humidity, heater as temperature heater and mist maker as a mist maker to increase humidity. The working systematics of the tool if the DHT22 sensor reads a temperature below 31°C then the heater will automatically turn on to raise the temperature and when the DHT22 sensor reads the humidity is less than 76% then the mist maker will lit to increase the humidity of the cage. So that this research is able to monitor cricket cages automatically with temperature between 20°C to 32°C and humidity ranging from 65% to 80%.